Equal pay - NUPE leaflet 1988 (1988)
1988 1960-2000 "Equal pay - NUPE leaflet 1988" [EP0003a.jpg], 1988 This leaflet, issued by the National Union of Public Employees in 1988, calls for improvements in the provisions and implementation of equal pay legislation.